1988
DOI: 10.1002/hep.1840080418
|View full text |Cite
|
Sign up to set email alerts
|

Decreased collagen accumulation by a prolyl hydroxylase inhibitor in pig serum-induced fibrotic rat liver

Abstract: Hepatic fibrosis was induced in rats by repeated i.p. injections of pig serum. The hepatic hydroxyproline content increased to 2.1 times the normal control level at 6 weeks and to 3.2 times at 10 weeks. When P-1894B, an inhibitor of prolyl hydroxylase, was administered, there was a dose-dependent inhibition of the increase to nearly normal control levels at 6 and 10 weeks. There was also by histology a dose-dependent reduction in the degree of hepatic fibrosis. Hepatocellular damage was minimal and its extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Six of them had a sustained clinical response to treatment with concomitant normalization of serum PIIINP. 30 In an earlier study using the toxic P4H inhibitor, vineomycin A1, in pig serum-induced liver fibrosis in rats, the antifibrotic effects (measured as Hyp of the liver) correlated significantly (r ϭ .830) with mortality in the treatment groups, 31 suggesting that the decrease in Hyp in this study is caused by the death of the most severely ill animals. The compound also inhibited collagen synthesis in tissues other than the liver.…”
Section: Discussionmentioning
confidence: 46%
“…Six of them had a sustained clinical response to treatment with concomitant normalization of serum PIIINP. 30 In an earlier study using the toxic P4H inhibitor, vineomycin A1, in pig serum-induced liver fibrosis in rats, the antifibrotic effects (measured as Hyp of the liver) correlated significantly (r ϭ .830) with mortality in the treatment groups, 31 suggesting that the decrease in Hyp in this study is caused by the death of the most severely ill animals. The compound also inhibited collagen synthesis in tissues other than the liver.…”
Section: Discussionmentioning
confidence: 46%
“…A similar type of hepatic fibrosis can be induced in rats by repeated injections of equine serum, egg yolk, and human albumin, but not by treatment with rat serum, human γ-globulin, or ovalbumin [21,27]. A variety of studies exploring the effects of chemicals in liver fibrosis has been reported [12,15,31,35]. Carbon tetrachloride (CCl 4 )-induced rat liver cirrhosis following hepatocellular necrosis has also been used as a model for investigating liver fibrogenesis in comparison with PS-induced fibrosis [15,22,26].…”
Section: Animalsmentioning
confidence: 99%
“…In addition, the number of mitotic hepatocytes in the left lateral lobe tissue sections of control and treated rats from Experiments II and III was counted. In Experiment II, the extent of fibrosis in each lobe of the liver was classified in 4-grades (Grades 1: early stage; Grades 2 and 3: late stage: Grade 4: advanced stage) following to Fujiwara et al [12] to facilitate interlobar comparison. To compare the extent of hepatic fibrosis in between individual rats, the left lateral lobe of each liver was investigated.…”
Section: Animalsmentioning
confidence: 99%
“…In addition, histopathological comparison between the late (Experiment I) and early (Experiment II) fibrous septa (FS) was also performed on serial sections. The extent of hepatic fibrosis was evaluated according to Fujiwara's description [6] with slight modification.…”
Section: Animalsmentioning
confidence: 99%